ORGANIZATIONAL CULTURE, UNIVERSITY-INDUSTRY COLLABORATION STRATEGIES, AND INNOVATION PROGRAMS IN UNIVERSITIES: THE MODERATING ROLE OF GOVERNMENT FUNDING - Islamiyah, Zakiyah Tsauroh; Rahayu, Agus; Disman, Disman; Wibowo, Lili Adi (Universitas Padjadjaran, 2024)
This study examines the effects of organizational culture, university-industry collaboration strategies, and government funding on innovation programs in Indonesian public universities. The research objectives were to identify the key factors that influence innovation outcomes and explore the moderating role of government funding. A quantitative research approach was adopted focusing on 73 public universities in Indonesia. Data were collected using a structured questionnaire distributed to senior administrators and faculty members involved in innovation programs and university-industry collaborations. The key variables measured included organizational culture, university-industry collaboration strategies, innovation programs, and government funding, using a 7-point Likert scale. A multiple linear regression analysis was conducted to test the hypothesized relationships and interaction effects. The findings reveal that organizational culture and university-industry collaboration strategies significantly enhance innovation programs, with government funding amplifying these effects. A larger university size was found to negatively impact innovation outcomes, while overall funding levels had a positive but smaller effect than other variables. The results highlight the importance of fostering supportive organizational cultures, developing robust collaboration strategies, and securing adequate government funding to drive innovation in academic institutions. Future research should explore the additional factors that influence innovation outcomes in various contexts. Recommendations include strengthening university-industry partnerships and advocating for sustained government support to enhance the innovation capacity of universities. Penelitian ini mengkaji dampak budaya organisasi, strategi kolaborasi universitas-industri, dan pendanaan pemerintah terhadap program inovasi di universitas negeri di Indonesia. Tujuan penelitian adalah untuk mengidentifikasi faktor kunci yang mempengaruhi hasil inovasi dan mengeksplorasi peran moderasi pendanaan pemerintah. Pendekatan penelitian kuantitatif diadopsi, dengan fokus pada 73 universitas negeri di Indonesia. Data dikumpulkan menggunakan kuesioner terstruktur yang didistribusikan kepada administrator senior dan anggota fakultas yang terlibat dalam program inovasi dan kolaborasi universitas-industri. Variabel kunci yang diukur termasuk budaya organisasi, strategi kolaborasi universitas-industri, program inovasi, dan pendanaan pemerintah, menggunakan skala Likert 7 poin. Analisis regresi linier berganda dilakukan untuk menguji hubungan dan efek interaksi yang dihipotesiskan. Temuan menunjukkan bahwa budaya organisasi dan strategi kolaborasi universitas-industri secara signifikan meningkatkan program inovasi, dengan pendanaan pemerintah memperkuat efek ini. Ukuran universitas yang lebih besar ditemukan berdampak negatif terhadap hasil inovasi, sementara tingkat pendanaan secara keseluruhan memiliki efek positif tetapi lebih kecil dibandingkan dengan variabel lainnya. Hasil ini menyoroti pentingnya membina budaya organisasi yang mendukung, mengembangkan strategi kolaborasi yang kuat, dan mendapatkan pendanaan pemerintah yang memadai untuk mendorong inovasi di institusi akademik. Penelitian lebih lanjut harus mempertimbangkan untuk mengeksplorasi faktor tambahan yang mempengaruhi hasil inovasi dalam konteks yang berbeda. Rekomendasi termasuk memperkuat kemitraan universitas-industri dan mengadvokasi dukungan pemerintah yang berkelanjutan untuk meningkatkan kapasitas inovasi universitas.